ANALISIS BIBLIOMETRIK: OVERCONFIDENCE CEO DAN PENGHINDARAN PAJAK - Nanik Lestari; Bambang Sutopo (Universitas Trilogi, 2025)
The study analyses global publication trends on Tax Avoidance and CEO Overconfidence using a bibliometric approach based on Scopus data from 23 articles. Findings reveal that measurement methods for both variables are inconsistent, highlighting the need for more robust methodologies. Future research should: Expand to cross-country contexts considering cultural and institutional differences. Include firms of various sizes for better generalization. Develop accurate CEO characteristic measures (e.g., narcissism, facial masculinity, tax competence) using psychometrics, text analysis, or AI. Examine interactions with other managerial roles (CFOs, tax advisors) and corporate governance mechanisms (board independence, analyst monitoring, institutional ownership). Apply advanced models (mediation, moderation, moderated mediation) for stronger validity. Explore emerging economies (Russia, India, Brazil) and ethical issues like CSR and gender diversity at leadership levels for broader insights.Keywords: Corporate Tax Avoidance; Characteristic CEO, Overconfidence CEO; Tax Avoidance